Solubility determination and modelling for phthalimide in mixed solvents of (acetone, ethyl acetate or acetonitrile + methanol) from (278.15 to 313.15) K. (March 2017) - Li, Yanxun; Li, Congcong; Du, Cunbin; Cong, Yang; Cheng, Chao; Zhao, Hongkun
Graphical abstract: Highlights: Solubility of phthalimide solubility in three binary mixed solvents were determined. Solubility data were correlated and calculated by four models. The standard dissolution enthalpy for the dissolution processes were computed. Abstract: The solubilities of phthalimide in mixed solvents of (acetone + methanol), (ethyl acetate + methanol) and (acetonitrile + methanol) were determined experimentally by using the isothermal dissolution equilibrium method within the temperature range from (283.15 to 318.15) K under atmospheric pressure (101.1 kPa). For the three systems of (acetone + methanol), (ethyl acetate + methanol) and (acetonitrile + methanol), at a fixed composition of acetonitrile, acetone or ethyl acetate, the solubility of phthalimide increased with an increase in temperature; however, at the same temperature, they increased at first and then decreased with the increase in mass fraction of acetonitrile, acetone or ethyl acetate. At the same temperature and mass fraction of acetonitrile, acetone or ethyl acetate, the mole fraction solubility of phthalimide in (acetone + methanol) was greater than those in the other mixed solvents. The solubility values obtained were correlated with Jouyban-Acree model, van't Hoff-Jouyban-Acree model, modified Apelblat-Jouyban-Acree model and CNIBS/R-K model. The maximum values of relative average deviations ( RAD ) and root-mean-square deviations ( RMSD ) between the experimental and calculated solubility were 5.64 × 10 −2 and 11.56 × 10 −4, respectively. The CNIBS/R-K model proved to provide the best representation of the experimental results. In addition, the standard dissolution enthalpies of the dissolution process were calculated on the basis of the measured solubility. Dissolution of phthalimide in these mixed solvents is an endothermic process.